Take a “Selfie”: Examining How Leaders Emerge From Leader Self-Awareness, Self-Leadership, and Self-Efficacy - Bracht, Eva M.; Keng-Highberger, Fong T.; Avolio, Bruce J.; Huang, Yiming (Frontiers in Psychology, 2021)
It is important to understand the processes behind how and why individuals emerge as leaders, so that the best and most capable individuals may occupy leadership positions. So far, most literature in this area has focused on individual characteristics, such as personality or cognitive ability. While interactions between individuals and context do get research attention, we still lack a comprehensive understanding of how the social context may help individuals to emerge as leaders. Such knowledge could make an important contribution towards getting the most capable, rather than the most dominant or narcissistic individuals, into leadership positions. In the present work, we contribute towards closing this gap by testing a mediation chain linking a leader’s leader self-awareness to a follower’s leadership emergence with two time-lagged studies (nstudy1 = 449, nstudy2 = 355). We found that the leader’s leader self-awareness was positively related to (a) the follower’s leadership emergence and (b) the follower’s nomination for promotion, and that both relationships were serially mediated by the follower’s self-leadership and the follower’s leader self-efficacy. We critically discuss our findings and provide ideas for future research.